Permanent pacemaker implantation following mitral valve surgery: a retrospective cohort study of risk factors and long-term outcomes. (28th February 2021) - Helmers, Mark R; Shin, Max; Iyengar, Amit; Arguelles, Gabriel R; Mays, Jarvis; Han, Jason J; Patrick, William; Altshuler, Peter; Hargrove, W Clark; Atluri, Pavan
Abstract: OBJECTIVES: Conduction disturbances requiring permanent pacemaker (PPM) implantation remain a complication following valvular surgery. PPMs confer the risk of infection, tricuspid valve regurgitation and pacing-induced cardiomyopathy. Literature examining PPM placement in mitral valve surgery (MVS) is limited. METHODS: Our institutional mitral valve (MV) database was retrospectively reviewed for adult patients undergoing surgery from 2011 to 2019. Patients with preoperative PPM were excluded. Patients were stratified by the receipt of PPM following their index operations. Multivariable logistic regression was performed to determine patient and operative risk factors for PPM. Subgroup analysis was performed on patients who underwent isolated MVS. Kaplan–Meier analysis and a multivariable Cox proportional hazards model were utilized to assess the association between PPM implantation and long-term survival. RESULTS: A total of 3391 (2991 non-PPM and 400 PPM) patients met the study criteria. Significant predictors of PPM included increased decade of age (odds ratio: 1.23; 95% confidence interval: 1.12–1.35), concomitant aortic (1.44; 1.10–1.90) and tricuspid valve procedures (2.21; 1.64–2.97) and prior history of myocardial infarction (1.48; 1.07–1.86). In the isolated MV repair population, annuloplasty with ring prosthesis was associated with PPM (3.09; 1.19–8.02). Patients in the replacement population did not have significant identifiable risk factors. There was no survival difference found, and postoperative PPM placement was not found to be an independent predictor of mortality. CONCLUSIONS: Our primary aim was to elucidate predictors for PPM implantation in MVS and found increasing age and concomitant procedures to be risk factors. Receipt of PPM is associated with worse long-term survival but does not independently predict survival. Among patients undergoing isolated MV repair, use of an annuloplasty ring confers a higher risk of PPM compared to an annuloplasty band.